Penatalaksanaan Pencegahan Luka Diabetikum pada Penderita Diabetes Mellitus di RSUD Dr. Sukardjo Kota Tasikmalaya - Anwar H, Syaefunnuril; Robby, Asep; Agustin, Teti; Wayunah (Yayasan Inspirasi El Burhani, 2025)
Introduction: Diabetes mellitus is a chronic disease characterized by high blood glucose levels. The number of people with diabetes mellitus increases annually worldwide and in Indonesia, increasing the risk of complications. One common complication of diabetes mellitus is neuropathy in the lower extremities, which can lead to further complications, such as diabetic ulcers. Objective: Patients with diabetes mellitus treated at Dr. Sukardjo Regional Hospital in Tasikmalaya without complications of diabetic ulcers on the feet. Method: Subjects were given an explanation of the procedures to be performed, including a general assessment, foot assessment, health education on foot care, and a re-evaluation of their foot condition and care in the following three days. Result: Of the 16 patients, 9 complained of pain in the right and left calf areas, accompanied by numbness and tingling at rest and while walking. In addition, 2 patients experienced changes in the shape of their feet, accompanied by stiffness and swelling. After receiving education and a reassessment three days later, only six patients still complained of calf pain, and two participants still experienced changes in the shape of their feet, accompanied by stiffness and swelling. Conclusion: There was a reduction in the number of patients complaining of extremity pain between before and after receiving health education on foot care for preventing diabetic ulcers in patients with diabetes mellitus at Tasikmalaya City Hospital.